The Influence of Power on Post-Buyout Land Management Practices - Sumaira Niazi; Elyse Zavar; Alex Greer; Sherri Brokopp Binder (Histories)
U.S. government agencies execute home relocation programs, known as buyouts, in flood-prone areas to reduce hazard exposure. By converting the buyout properties into open space, these governmental agencies assume ownership and management responsibilities. As with all landscapes, the post-buyout landscape reflects power dynamics and institutional forces that shape how the land is managed, perceived, and used. For acquired properties, historic housing polices, disaster risk reduction strategies, and the social construction of the land have all accumulated over time on the post-buyout landscape and influence contemporary land management practices. To understand the influence of power and social capital on post-buyout land management, this study analyzes land management practices and compares them with the socioeconomic characteristics of buyout neighborhoods in Harris County, Texas, USA, a county with a fifty-year buyout history. Results indicate that homeownership status, race, and ethnicity were related to post-buyout land management to varying degrees, thus reflecting differing degrees of social capital in buyout neighborhoods and therefore power to shape the management of post-buyout open space.